Late-Onset Metastatic Malignant Spindle Cell Tumour Presenting with Massive Intra-Abdominal Haemorrhage - Pamathy Gnanaselvam; Malintha Lahiru; Mariathas Priatharshan; Umesh Jayarajah; Kathirvetpillai Kopinath (Case Reports in Surgery)
Primary spindle cell sarcoma is a rare tumour. The presentation of acute intra-abdominal bleeding from a metastatic spindle cell tumour has not been previously reported. We report a case of a 40-year-old woman with a history of curative resection of the medial compartment of the right thigh for spindle cell sarcoma presenting with an acute onset abdominal pain and haemorrhagic shock after 5 uneventful years. Emergency exploratory laparotomy was conducted that revealed a retropancreatic mass which had ruptured along its inferior border. Histological evaluation revealed a metastatic deposit of the spindle cell sarcoma. In cases of spontaneous abdominal haemorrhage, it is important to consider the possibility of a ruptured metastatic deposit among the differentials especially in patients with a history of malignancies. Moreover, this is the first reported case of metastatic malignant spindle cell sarcoma presenting with intra-abdominal haemorrhage.